Strategies in Raising Speaking Performance for Communication Students: A Case Study at Universitas Bunda Mulia - Yasinta Deka Widiatmi (Universitas Bunda Mulia, 2020)
Nowadays communication is a very important. Communication helps people to understand other people from around the world. If we communicate, it means we can understand their language because people usually use language to communicate. As a result, mastering English is also one of keys to compete and to face global competitions for students in finding the best job in the world. English is a foreign language for Indonesian students. Therefore, the students have difficulties in learning English. The reason is that they only learn English only in the classroom. The materials they get in the classroom are only grammar. Therefore, the students only learn English theoretically. They do not have much time to practice their English both inside and outside the class. The objectives of this study are first, to find out the problem they face when learning English Subject. Second, to find out the strategies in raising English performance for Communications students in Universitas Bunda Mulia. This is a case study at Universitas Bunda Mulia.